Association of diabetes with stroke and post‐stroke dementia: A population‐based cohort study. Issue 7 (2nd June 2020) - Shang, Ying; Fratiglioni, Laura; Marseglia, Anna; Plym, Anna; Welmer, Anna‐Karin; Wang, Hui‐Xin; Wang, Rui; Xu, Weili
Abstract: Introduction: The impact of prediabetes and diabetes on stroke and the development of dementia after a stroke remain unclear. Methods: A total of 2655 dementia‐free participants (including a stroke‐free cohort and a prevalent stroke cohort) were followed‐up for 12 years. Dementia and post‐stroke dementia were determined by clinical examinations and national registry data. Diabetes was ascertained via medical examination, medication use, medical records, or glycated hemoglobin (HbA1c) ≥6.5%. Prediabetes was defined as HbA1c ≥5.7% in diabetes‐free participants. Results: In the stroke‐free cohort, 236 participants developed ischemic stroke, and 47 developed post‐stroke dementia. Diabetes was associated with ischemic stroke (hazard ratio [HR] 1.76, 95% confidence interval [CI] 1.16 to 2.67) and post‐stroke dementia (HR 2.56, 95% CI 1.04 to 6.25). In the prevalent stroke cohort, diabetes was also related to dementia risk. Prediabetes was not significantly related to stroke or post‐stroke dementia. Discussion: Diabetes, but not prediabetes, is associated with an increased risk of ischemic stroke and post‐stroke dementia.